Interval type 2- fuzzy rule based system approach for selection of alternatives using TOPSIS - Yaakob, Abdul Malek; Gegov, Alexander; Ku Khalif, Ku Muhammad Naim; Abdul Rahman, Siti Fatimah (2015)
The paper considers fuzzy rule based system for multi criteria group decision making problem. A novel version of TOPSIS method using interval type 2 fuzzy rule based system approach is proposed with the objective of improving the type 2 TOPSIS ability to deal with ambiguity through the combination of the mathematical process involved in the type 2 TOPSIS with the expert empirical knowledge. On the other hand, a hybrid analysis of decision making process that requires the use of human sensitivity to reflect influence degree of decision maker can be expressed by a fuzzy rule base. To ensure practicality and effectiveness of proposed method, stock selection problem is studied. The ranking based on proposed method is validated comparatively using Kendall’s Tau rank correlation. Based on the result, the proposed method outperforms the established non-rule based version of type 2 TOPSIS in term of ranking performance.